An Introduction to Tissue Engineering and Orthopedic Applications - Fatemeh Baghaie Nia; Fatemeh Khavari; Masoumeh Firouzi; Mohammad Hossein Nabian (Journal of Orthopedic and Spine Trauma, 2020)
Nowadays, orthopedic-related pathologic conditions are considered as a growing concern. Also, the conventional treatments (grafting techniques) are not efficacious enough for the growing clinical needs. In the last decades, researches have been focused on finding more effective alternative treatments. Tissue engineering (TE) is a newly emerging field of science that has great potential to reduce these clinical issues. There are three main components in TE including cells, biomaterials, and signals. Choosing the best combination of these components is a vital decision in a TE process. In this review article, we are going to discuss TE and its components and also highlight some of the researches in the field of orthopedic TE by focusing on some tissues including bone, cartilage, skin, skeletal muscle, peripheral nervous system (PNS), tendon, and ligament. In the end, TE, as a new field of science, faces some major challenges that we will address some of them in this article.